Measuring regional income disparities in LDCs - Olaf Hübler (Intereconomics, 1976)
The problem of income disparities in developing countries is constantly gaining in importance. Clearly a pure growth strategy alone cannot be effective and disparities are steadily increasing. What is needed for an effective policy first of all are adequate statistics and indicators.
Keywords: 330; Regional Policy